Ototoxicity in children receiving cisplatin chemotherapy - Hee Jin Jang; Hyung Rae Cho; Jae Hee Lee; Kun Yuk Bae; Jong Jin Seo; Hyung Nam Moon; Ho Joon Im (Korean Pediatric Society, 2010)
Purpose : Cisplatin is highly effective for the treatment of solid tumors in children. However, the clinical use of cisplatin is limited by its ototoxicity. The aim of this study was to evaluate the ototoxicity in children treated with cisplatin. Methods : We performed a single institution retrospective analysis of pediatric oncology patients who received cisplatin therapy between January 2001 and January 2008. Thirty-seven patients with sufficient medical and audiologic data were included in this study. Results : The median age at the time of diagnosis was 10.7 (range 3.8–16.7) years. There were 16 males and 21 females. The underlying diseases were osteosarcoma (15 cases), medulloblastoma (14 cases), germ cell tumors (7 cases), and hepatoblastoma (1 case). The median individual dose was 100 mg/m2/cycle (56-200). The median cumulative dose was 480 mg/m2 (200-1,490). Sixteen patients (43%) received cranial radiotherapy. Of the 37 patients, 17 developed hearing loss, leading to an overall incidence of 46%. Logistic regression showed that age at treatment (P=0.04) and cumulative dose of cisplatin (P=0.005) were the significant risk factors in predicting hearing loss in children treated with cisplatin. In all the patients who had hearing loss, there was neither improvement nor aggravation during the follow-up (3–68 months). Conclusion : The cumulative dose of cisplatin (>500 mg/m2) and younger age at treatment (<12 years) were 2 most important risk factors for ototoxicity in patients treated with cisplatin. Serial audiometric evaluations are needed in the patients with risk factors during and after cisplatin treatment.